Variable correlation between production and efficiency in response to supplement in lactating cows Guzerat - Silva, Arthur; Sousa, Breno Mourão de; Silva, Ricardo Reis e; Borges, Ana Luiza Costa Cruz; Costa, Isabela Carvalho; Barata, Frederico Guimarães; Carvalho, Pedro Henrique de Araújo; Silva, Ana Luiza Moreira (Pubvet, 2018)
ABSTRACT. Research in specialized nutrition for zebu cattle in Brazil are somewhat advanced and widespread, specialize and deepen the scientific knowledge about the physiology and production characteristics of this group are of great value to breeders, since the livestock industry is becoming increasingly competitive and the producer's profit is highly correlated with the productivity of each animal. Thus, the present study evaluated in an unprecedented manner and described the efficiency of response to supplementation in cows Guzerat, defining ideas feeding levels for different milk production. 109 cows pure source between primiparous and multiparous supplemented which were on average 3.42 kg/day and the average milk production 10,42kg/day were used. Guzerat cows have MR = 2.32, and it is highly correlated with days in milk, lactation numbers and milk production.
Keywords: efficiency; guzerat; milk; nutrition; ruminants